WP1-22 DuraGen™ as an encapsulating material for neural stem cell delivery. Issue 3 (14th February 2019) - Finch, L; Harris, S; Adams, C; Sen, J; Tickle, J; Tzerakis, N; Chari, DM
Abstract : Objectives: Achieving neural regeneration after spinal cord injury (SCI) represents a significant challenge. Neural stem cell (NSC) therapy offers replacement of damaged cells and delivery of pro-regenerative factors, but >95% of cells die when transplanted to sites of neural injury. Biomaterial scaffolds provide cellular protective encapsulation to improve cell survival. However, current available scaffolds are overwhelmingly not approved for human use, presenting a major barrier to clinical translation. Surgical biomaterials offer the unique benefit of being FDA-approved for human implantation. Specifically, a neurosurgical grade material, DuraGen™, used predominantly for human duraplasty has many attractive features of an ideal biomaterial scaffold. Here, we have investigated the use of DuraGen™ as a 3D cell encapsulation device for potential use in combinatorial, regenerative therapies. Methods: Primary NSCs were seeded into optimised sheets of DuraGen™. NSC growth and fate within DuraGen™ were assessed using 3D microscopic fluorescence imaging techniques. Results: DuraGen™ supports the survival (ca 95% viability, 12 days) and 3D growth of NSCs. NSC phenotype, proliferative capacity and differentiation into astrocytes, neurons and oligodendrocytes were unaffected by DuraGen™. Conclusions: A 'combinatorial therapy', consisting of NSCs protected within a DuraGen™ matrix, offers a potential clinically translatable approach for neural cell therapy.